RESPON BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) TERHADAP ABU JANJANG KELAPA SAWIT PADA TANAH BEKAS TAMBANG BATUBARA DI POLYBAG - Padhila Sari; Gusniwati Gusniwati (Bioplantae, 2015)
This study aims to determine the response of oil palm seedlings to oil palm bunch ashand get the composition of palm bunch ash as the optimum media mix for planting oilpalm seedlings in the ex-coal mining soil in polybag. This study used a CompletelyRandomized Design (CRD) with 4 treatments, the composition between ex-coal miningsoil and oil palm bunch ash (75%:25%), (50%:50%), (25%:75%) and six replicates.The results showed that the composition of ex-coal mining soil and oil palm bunch ashhave significant effect on seedling height, seedling diameter, number of leaves, leafarea, dry weight and root dry weight. The composition between ex-coal mining soil andoil palm bunch ash (75%:25%) gave the best results to all parameter observed.